NATIONAL ROMANTICISM IN WALT WHITMAN POEMS - Tomi Arianto (Lire Journal (Journal of Linguistics and Literature), 2018)
Romanticism is often misunderstood as something genuine love and merely about romance. In fact, romanticism is an understanding of great ideas that also be delivered great ideas. The development of Romanticism delivered a new orientation that called National Romanticism by maintaining the freedom of individual, sovereignty, and independent of human rights. This study took data from three Walt Whitman poems; Patriotic, War Democracy, and Poem of America. Researcher was using the concept of interpretation to explore the meaning of poetry and the influence of romanticism in Whitman poetry. Researchers use Isaiah's theory in his book “the root of romanticism” to explore the influence of the romanticism idea on Whitman's poems. From the three samples of poetry, it is found that romanticism is very influential in Whitman poetry, especially the idea of romantic nationalism. Patriotic themes, nationalities and egalitarian concepts are reflected in Whitman's collection of "Leaves of grass" poems. Patriotic themes and nationalities are seen from the struggle for the right of individual freedom in opposing slavery and aristocratic government. The egalitarian concept is seen from the struggle to promote equality, as well as the democracy system that promotes people's sovereignty. The role of the idea of romanticism has evolved in American territory because it shares the same pattern and state of affairs as revolutions against noble, social, and political norms and rationalization of nature. Thus, the representation of romantic ideas originating from Western Europe of the 18th century has penetrated into the 19th century America which is reflected in the works that carried Whitman.